A Clinical Comparison between Plain Ropivacaine V/S Ropivacaine and Clonidine by Caudal Route for Post Operative Analgesia in Children - Vuyyuru Babu Rajendra Prasad (International Journal of Health and Clinical Research, 2021)
Background and objectives: Addition of clonidine to ropivacaine (0.25%) can potentially enhance analgesia without producing prolonged motor blockade. The aim of the present study was to compare the post-operative pain relieving quality of ropivacaine (0.25%) and clonidine mixture to that of plain ropivacaine (0.25%) following caudal administration in children.Method: After careful pre-anaesthetic check-up children posted for elective sub- umbilical surgeries between age groups of 2-10yrs of ASA I & II were randomly divided into Groups R and RC, of 30 each, injected with Inj. Ropivacaine 0.25% (1ml/kg body weight) and Inj. Ropivacaine 0.25% (1ml/kg) and Inj. Clonidine (2 mcg/kg) combination through caudal respectively prior to start of surgery after induction. Intra-op and post-operative duration of analgesia and motor blockade were noted along with other vital parameters.Results: Significantly prolonged duration of post operative analgesia was observed in Group RC. Heart rate and blood pressure was statistically different but not clinically. Neither motor blockade nor post operative sedation varied significantly between the groups.Conclusion: The combination of clonidine 2 mcg/kg and ropivacaine 0.25% 1ml/kg was associated with an improved quality of post-operative analgesia compared to plain ropivacaine 0.25% 1 ml/kg. The improved quality and duration of analgesia of the ropivacaine - clonidine mixture was achieved without causing any significant adverse effects or prolongation of motor blockade.